LANGUAGE DEVELOPMENT AND ITS IMPLICATION IN AN ESL CLASSROOM - Ogechukwu Mary Nwanna (Universitas Negeri Malang, 2025)
The study investigated language development and its implication in an ESL classroom. The study stated that children undergo different developmental stages in a bid to acquire and learn language(s). However, when the developmental does not augur well, there is every tendency that challenges would crop up. The study was guided by two research questions. Descriptive research design was adopted for the study. The sample used for the study was 326 primary school pupils. Instrument for data collection was structured questionnaire designed by the researcher. Means and standard deviation were used for data analysis. The result of the findings revealed that integration of developmental strategies/ programmes in lesson plan and developing oral skills and abilities have high impact on language development in children. It further revealed that poor verbal skills, limited vocabulary and difficulty in forming sentences were the challenges seen in language development among children as well. Some recommendations were made among which was that language developers and teachers which are major stimulants should be properly equipped and sensitized in order to handle and cope with children’s different language developmental stages.